Prediksi Genangan Banjir dengan Menggunakan Metode Rasional USSCS 1973 - Dana Rezky Arisandhy; Ananto Yudono; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2013)
Flooding that occurred in the Makassar City is 23 % of the total area of the city, that is 4086 ha. This floodwaters research is focused on Tamalanrea districts, which constitute the largest districts hit by floods about approximately 1684.59 ha. The spot selected region is BTN Hamzy, Antara ,and Asal Mula Housing. Flooding that occurred in this region is caused by changes in land use, poor drainage, sloping contours and form a basin area, and impermeable soil so that runoff contributes high . High rainfall can also cause floodwaters at this location. An understanding of the process and the amount of runoff and the influenced factors are very necessary as a reference in dealing with flood control. The purpose of this study was to determine the rate of surface runoff, extensive flooding, and flood inundation predictions, the effect of changes in rainfall intensity on surface runoff. Analysis procedure is conducted to calculate the rate of runoff using USSCS 1973 rational methods with variables: land cover, soil type, and slope contour, area, and intensity of rainfall. The results of these calculations are compared with the volume of land each contour and intensity of rain to predict floodwaters and the effect of rainfall intensity on surface runoff.